2020
DOI: 10.24136/oc.2020.010
|View full text |Cite
|
Sign up to set email alerts
|

Can discounts expand local and digital currency awareness of individuals depending on their characteristics?

Abstract: Research background: Because of enabling a greater amount of money circulation and addressing the needs of individuals in specific regions, local and digital currencies have become more important for local economic and sustainable development, especially in last decade. However, their awareness by potential users have become one of major constraints to their extensive usage. In this regard, discount have been used to increase the awareness of individuals.  Purpose of the article: As discount is used as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…The Wall Street Journal (Kesmodel, 2006) also states that only 25% of consumers who searched for products online actually bought them online. Another survey showed that 65% percent of online consumers did not complete their purchase due to feelings of uncertainty about the credibility of the seller or the information on the website or presentation of the products they sell (Ključnikov et al, 2020;Ungerman et al, 2018). This earlier research shows that consumers remain to some extent insecure about e-commerce transactions.…”
Section: Literature Reviewmentioning
confidence: 95%
“…The Wall Street Journal (Kesmodel, 2006) also states that only 25% of consumers who searched for products online actually bought them online. Another survey showed that 65% percent of online consumers did not complete their purchase due to feelings of uncertainty about the credibility of the seller or the information on the website or presentation of the products they sell (Ključnikov et al, 2020;Ungerman et al, 2018). This earlier research shows that consumers remain to some extent insecure about e-commerce transactions.…”
Section: Literature Reviewmentioning
confidence: 95%
“…Smart contracts are "programs that automatically execute when pre-specified conditions (i.e., rules) in the protocols are satisfied" (Ključnikov et al, 2020).…”
Section: Decentralized Contractingmentioning
confidence: 99%
“…The definition mentioned above also supports the idea of Etezadzadeh (2016) that the main function of the city is to provide access to any benefit, good or service for the city inhabitants. In this regard, local digital currencies might be an example that provides economic and social benefits for city inhabitants (Ključnikov et al 2020a; Ključnikov et al, 2020b;Civelek et al, 2019;Civelek et al, 2021b). The growth of the urban population requires ensuring access to all urban opportunities for the increased number of people, while many city departments are not supposed for servicing such a great amount of the population, though they must create a liveable and sustainable environment for its citizens (Wataya & Shaw, 2019).…”
Section: Introductionmentioning
confidence: 99%